Psihološki učinki skrajne gibalne neaktivnosti v pogojih simulirane breztežnosti - Dolenc, Petra (Psihološka obzorja (Ljubljana), 2009)
Long-duration weightlessness simulated by bed rest represents an important model to study the consequences of physical inactivity and sedentarism on the human body. This study evaluated changes of mood status, psychological well-being, coping strategies and physical self in ten healthy young male subjects during a 35-day horizontal bed rest. Participants were asked to complete psychometrical inventories before and after the bed rest experiment. The preceived satisfaction with life and the physical self-concept did not change during bed rest period and mood states were relatively stable during the experiment according to the Emotional States Questionnaire. The neurotic level was enhanced during the bed rest period according to the Slovenian version of the General Health Questionnaire. However, even after the period of physical immobilization, the expression of these symptoms remains relatively low and does not represent a risk to the mental health of the subjects. The results from Coping Resources Inventory indicated a tendency toward an increase of emotion focused coping and a decrease of problem focused coping strategies. The importance of this research was to provide evidence that the provision of favourable habitability countermeasures can prevent deterioration in the psychological state under conditions of physical immobilisation. Our findings have applied value in the field of health prevention and rehabilitaion.
Keywords: gibalna neaktivnost; psihologija; psychology; simulirana breztežnost